Peningkatan Penguasaan Konsep dan Struktur Ilmu Guru Teknik Otomotif Melalui Diseminasi Teknologi Controlled Area Network Bus (CAN Bus) di SMKN Palang - Fuad Indra Kusuma; Mindarta, Erwin Komara; Rudi Nurdiansyah; Muhammad Mukhsin J.; Sandi Surya Wijaya (CV. IRA PUBLISHING, 2023)
The quality of vocational school teachers is seen as needing to be improved. This is shown by the high number of vocational school teachers who do not yet have teaching or skill competency certificates. Educator certification indicates that the teacher has been declared to have met the requirements and passed the competency test to become a professional teacher. On the other hand, a skills competency certificate indicates vocational school teachers who are experts in their skills competency in terms of concept and knowledge structure. The problem is that not all teachers have the opportunity to take part in programs/training organized by the government or private sector to improve their mastery of scientific concepts and structures. The community service implementation team from the UM Automotive Engineering Education Undergraduate study program provides training specifically for automotive engineering teachers at vocational schools to transfer the latest knowledge related to automotive advanced, namely CAN Bus, to increase teachers' mastery of concepts and structures. Training methods include site surveys, formulating training materials, making schedules, preparing tools and materials, and training instructors up to evaluation. The CAN Bus training was held offline in accordance with health protocols, and the result was an increase in teachers' mastery of concepts and knowledge structures as evidenced by the mean posttest score (70.29) > mean pretest score (62.11), and the difference was real Sig. (2-tailed) of 0.000 at 0.05. Apart from that, from the resource person's explanation, the teacher knows how to teach CAN Bus to students.